2022
DOI: 10.1149/ma2022-02411513mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electrochemical Behavior of High-Temperature Ionomer Blends

Abstract: In the past two years, tremendous improvements in high-temperature polymer electrolyte membrane fuel cells (HT-PEMFCs)(1) and HT-PEM hydrogen pumps(2) using membrane electrode assemblies containing ion-pair HT-PEMs(3, 4) and electrode phosphonic acid ionomer binders. A challenge in using phosphonic acid ionomers at high temperatures and under anhydrous conditions is their propensity to form anhydrides that compromise ionic conductivity(5). Poly(tetraflurostyrene phosphonic acid-co-pentafluorostyrene) (PTFSPA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[ 46b,47b,223 ] Arges and co‐workers elucidated that the proton conductivity of protonated phosphonic acids is improved due to the suppressed anhydride formation of phosphonic acids. [ 224 ] Due to the enhanced proton conductivity, the kinetic performance of HT‐PEMFC greatly improved (66 mA cm −2 for protonated phosphonic acid ionomer versus 19 mA cm −2 for non‐protonated phosphonic acid ionomer at 0.8 V, 160 °C under H 2 /air conditions). [ 47b ]…”
Section: Design Strategy Of Hydrocarbon Ionomer‐bonded Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 46b,47b,223 ] Arges and co‐workers elucidated that the proton conductivity of protonated phosphonic acids is improved due to the suppressed anhydride formation of phosphonic acids. [ 224 ] Due to the enhanced proton conductivity, the kinetic performance of HT‐PEMFC greatly improved (66 mA cm −2 for protonated phosphonic acid ionomer versus 19 mA cm −2 for non‐protonated phosphonic acid ionomer at 0.8 V, 160 °C under H 2 /air conditions). [ 47b ]…”
Section: Design Strategy Of Hydrocarbon Ionomer‐bonded Electrodesmentioning
confidence: 99%
“…[ 52b ] The capability of secondary pore structures of aprotic solvents was investigated using protonated phosphonic acids. [ 224 ] It was found that solvents with low pK a , such as dimethylsulfoxide (DMSO) (pK a of protonated DMSO = −2.48) push the protons back to the polymer acids, thus keeping them to a more non‐dissociated state, and resulting in less‐porous films. Aprotic solvents with high pK a , such as DMAc, DMF, and NMP (pK a of protonated solvents = −0.17 to −0.19) can create porous structures to improve fuel cell performance.…”
Section: Design Strategy Of Hydrocarbon Ionomer‐bonded Electrodesmentioning
confidence: 99%